ACCORD microvascular and Eye substudy: should the results change our practice?. (July 2011) - Cheng, Alice YY; Leiter, Lawrence A
SUMMARY   Microvascular complications of diabetes are potentially devastating and costly to both individuals and society. The United Kingdom Prospective Diabetes Study (UKPDS) and Steno-2 studies confirmed the benefits of glycemic control for reducing microvascular complications in Type 2 diabetes mellitus (T2DM) of short duration, but the benefits in people with T2DM of longer duration was not as clear. The Action to Control Cardiovascular Risk in Diabetes (ACCORD), Action in Diabetes and Vascular Disease: Preterax and Diamicron MR Controlled Evaluation (ADVANCE) and Veterans Affairs Diabetes Trial (VADT) studies were designed to address the question of macrovascular risk reduction in people with a longer duration of T2DM, but also looked at microvascular complications. Although the microvascular primary composite outcomes were not reduced in the ACCORD trial, seven of the 13 prespecified secondary outcomes were significantly reduced, and when considering those results along with the ACCORD-Eye substudy, one can conclude that there is reduction in retinopathy with intensive glycemic control. Nephropathy was also reduced in both the ADVANCE and ACCORD studies. As for peripheral neuropathy, ADVANCE did not show a reduction, but the assessment method was unclear. The ACCORD study did demonstrate significant reduction in three of the four prespecified neuropathy elements –– an important finding in an area with limited effective therapies. VADT was the only study to show no microvascular benefit at all, however, it had the smallest sample size, as well as the oldest and the most advanced population of all of the studies, which may account for the discrepancy. Therefore, the evidence to date supports that intensive glycemic control is effective in reducing microvascular complications among people with T2DM. However, although microvascular complication reduction is worthwhile, one must consider the patient as a whole and individualize the targets and consider the overall risk (including hypoglycemia):benefit ratio.